Productivity Effect of Adopting Environmental Management Measures Integrated with Labor Investments after the COVID-19 pandemic in Indonesian Enterprises - Nguyen, Tung Nhu (Journal of Ecohumanism, 2025)
Recent statistics have shown that carbon dioxide emissions in Indonesia are increasing due to its booming economy. However, the adoption of environmental management measures consumes labor for their execution, which may reduce manufacturing outputs due to the extracted workforce. Previous literature reported mixed results of environmental investments in different production contexts. This paper examines how the adoption of environmental management measures influences labor productivity in Indonesian enterprises. The regression analysis results of a World Bank Enterprise Survey for Indonesia in 2023 show that increasing labor investments such as wages, training, and bonuses, significantly increase the positive impact of the adoption of environmental management on labor productivity. The finding indicates that with more significant labor inputs, the adverse impact of environmental management on labor productivity diminishes. The study results suggest that firms should integrate their investments in environmental management with labor inputs to leverage productivity.